2017
DOI: 10.5194/gmd-10-3745-2017
|View full text |Cite
|
Sign up to set email alerts
|

A representation of the phosphorus cycle for ORCHIDEE (revision 4520)

Abstract: Abstract. Land surface models rarely incorporate the terrestrial phosphorus cycle and its interactions with the carbon cycle, despite the extensive scientific debate about the importance of nitrogen and phosphorus supply for future land carbon uptake. We describe a representation of the terrestrial phosphorus cycle for the ORCHIDEE land surface model, and evaluate it with data from nutrient manipulation experiments along a soil formation chronosequence in Hawaii.ORCHIDEE accounts for the influence of the nutri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 100 publications
5
136
0
Order By: Relevance
“…However, recent work has suggested an increasing role of nutrients limiting the productivity of ecosystems; both data and modeling efforts have shown that carbon dioxide (CO 2 ) uptake by terrestrial ecosystems strongly depends on nutrient availability (Bonan 2008, Peñuelas et al 2013, Fernandez-Martinez et al 2014. This has instigated the implementation of the effects of nutrient stocks and cycling in land-surface models (Wang et al 2010, Zaehle and Friend 2010, Goll et al 2012, 2017 and stressed the need for a profound and mechanistic understanding of nutrient cycling effects on the C cycle. Nitrogen (N) is of particular interest, being one of the important macronutrients to sustain plant life.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has suggested an increasing role of nutrients limiting the productivity of ecosystems; both data and modeling efforts have shown that carbon dioxide (CO 2 ) uptake by terrestrial ecosystems strongly depends on nutrient availability (Bonan 2008, Peñuelas et al 2013, Fernandez-Martinez et al 2014. This has instigated the implementation of the effects of nutrient stocks and cycling in land-surface models (Wang et al 2010, Zaehle and Friend 2010, Goll et al 2012, 2017 and stressed the need for a profound and mechanistic understanding of nutrient cycling effects on the C cycle. Nitrogen (N) is of particular interest, being one of the important macronutrients to sustain plant life.…”
Section: Introductionmentioning
confidence: 99%
“…Global ecosystem models are progressively incorporating dynamic N and P cycles to test their control on the global C balance (Buendía et al, 2014;Goll et al, 2012Goll et al, , 2017Yang et al, 2014). The land surface model CABLE considers C, N, and P dynamics and has previously been employed to estimate the control of N and P limitation on the historical and future global C balance (Y.-P. Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…At all three sites, nutrient availability is suboptimal when computed prognostically, this is indicated by leaf carbon:nitrogen:phosphorus ratios of 744:30:1, 1264:38:1, and 983:36:1 for BR‐Ma2, BR‐Sa1, and BR‐Sa3, respectively, which are elevated compared to the optimal ratio in ORCHIDEE of 267:17:1 (Goll et al, ). Furthermore, the nitrogen addition experiment (supporting information Text S3) and the elevated leaf nitrogen:phosphorus ratios indicate that nitrogen availability is not limiting plant productivity at all sites.…”
Section: Resultsmentioning
confidence: 99%
“…It has a detailed representation of root phosphorus uptake and accounts for root zone depletion of phosphorus as a function of root phosphorus uptake and phosphate ions diffusion controlled transport from the soil pores to the root surface. The major interactions between water and phosphorus cycling (Figure ) in ORCHIDEE are (1) the positive dependence of phosphate mobility on soil moisture (Equation 23 in Goll et al, ), which affects the uptake of phosphate by roots (Equation 4 in Goll et al, ) and its availability for plant growth, (2) the positive dependence of microbial mineralization on soil moisture (Section 2.1.3 in Goll et al, ), (3) the direct dependence of plant growth on plant internal phosphorus availability (Equation 13 in Goll et al, ), and (4) the indirect dependence of the photosynthetic capacity (maximum carboxylation rate) on leaf phosphorus. The latter is a consequence of constraints on the elasticity of the leaf nitrogen:phosphorus ratio (Equation 11 in Goll et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation